(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Chronic kidney disease–mineral and bone disorder (CKD-MBD) is a highly prevalent complication in pediatric dialysis patients, encompassing biochemical imbalances, skeletal abnormalities, and extraskeletal consequences such as cardiovascular morbidity. This study investigates the prevalence, biochemical features, and clinical manifestations of mineral and bone metabolism disorders in children undergoing maintenance hemodialysis at the National Children’s Medical Center in Uzbekistan. The research further evaluates treatment strategies, their alignment with Kidney Disease: Improving Global Outcomes (KDIGO) and European Society for Paediatric Nephrology (ESPN) guidelines, and the outcomes achieved. Results highlight persistent challenges in achieving biochemical targets, with hyperphosphatemia, hypocalcemia, and vitamin D deficiency remaining widespread. Despite therapeutic advances, only 55% of patients met guideline-based targets simultaneously. The study underscores the urgent need for earlier intervention, advanced therapeutic access, and regionally tailored strategies to reduce skeletal deformities and cardiovascular morbidity while enhancing quality of life.